Cinema de casa de reza: as relações entre tecnologia e cultura presentes nas práticas fílmicas da Associação Cultural de Realizadores Indígenas (ASCURI) de Mato Grosso do Sul - Gorges, Maria Claudia (2022)
The Cultural Association of Indigenous Filmmakers (ASCURI) of Mato Grosso do Sul is made up of indigenous from the Guarani, Kaiowá and Terena peoples and has been making films and producing training workshops in the villages since 2008. The objective of this thesis is to reflect on the filmic practices of ASCURI, considered here as ways of building alliances with audiovisual and cinema, which will also be called guaranization practices. For the construction of this thesis, we established a dialogue with members of ASCURI, through interviews, telephone conversations and meetings resulting from the construction of partnerships in events. We also went through some experiences of indigenous peoples with audiovisual and cinema, inserted both in the context of representation and self-representation of their images, bringing the variations that occur in these projects, understanding that the cinema produced with and by indigenous peoples is extensive, diverse and it is in many places, with ASCURI being one of those ways of making cinema. We analyzed a set of films produced about, with and by indigenous filmmakers, as well as archival photographs and images posted on social networks. We carried out historical research of the moments in which these projects were articulated. We also went through the projects that were fundamental for the constitution of ASCURI as an association. We conclude by addressing one of the most recent projects that ASCURI developed during the Covid-19 pandemic, the web series Nativas Narrativas: mirando mundos possíveis (ASCURI, 2020). The theoretical foundation is based on the reflections of sociologist Silvia Rivera Cusicanqui (2010, 2015, 2018) on the concepts of ch’ixi, interculturality and identification processes, which distance us from essentialist perspectives and invite us to inhabit the contradiction; in the questions of the indigenous thinker and activist Ailton Krenak (2019, 2020) about the concept of humanity and the imposition of a monoculture of thought; in the reflections of the philosopher Andrew Feenberg (2010, 2017) on technology, who, with his critique of technological determinism, proposes to think about the multiple narratives about technology. In this process, the alliances that ASCURI builds with audiovisual and cinema affects these technologies as they are transformed into modes of resistance, or rather, of existence, expression and sociability reproduction, in a Casa de Reza cinema.